2016
DOI: 10.20448/journal.522/2016.2.2/522.2.63.69
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peer Counselors in the Promotion of Student Discipline in Ugunja Sub-County, Kenya

Abstract: In spite of the existence of guidance and counseling services in schools in Siaya County for the management of discipline, in 2012, 32 schools went on the rampage. This scenario was suspected to be occasioned by lack of an effective alternative strategy to contain student indiscipline. The purpose of this study was to determine the role of peer counseling in promoting discipline among students in public secondary schools in Ugunja Sub-County, Kenya. The study adopted descriptive survey design. The population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
1
9
0
2
Order By: Relevance
“…This implies that statistically the more peer counselling programs are implemented in school, the more likely effective management of teenage pregnancies among the individual female students would be, given that they would less likely engage in sexual activities that result into teenage pregnancies. This finding agrees with Osodo, Mito, Raburu and Aloka (2016) study which reported that peer counselling has a significant role in promoting discipline among students in public secondary schools. On the contrary, Sigilai and Bett (2013) found that Headteachers and Teacher Counselors negatively perceived the effectiveness of peer counselling among their learners.…”
Section: Role Modelssupporting
confidence: 92%
See 1 more Smart Citation
“…This implies that statistically the more peer counselling programs are implemented in school, the more likely effective management of teenage pregnancies among the individual female students would be, given that they would less likely engage in sexual activities that result into teenage pregnancies. This finding agrees with Osodo, Mito, Raburu and Aloka (2016) study which reported that peer counselling has a significant role in promoting discipline among students in public secondary schools. On the contrary, Sigilai and Bett (2013) found that Headteachers and Teacher Counselors negatively perceived the effectiveness of peer counselling among their learners.…”
Section: Role Modelssupporting
confidence: 92%
“…Education policymakers in Kenya have endorsed a whole school approach to guidance and counselling as a model of excellent practice for assisting learners and students with diverse challenges (Osodo, Osodo, Mito, Raburu, & Aloka, 2016). These include emotional and psychological disturbances, career decisions and growth, family concerns, and alternatives to corporal punishment.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above phenomena, it is necessary to develop counseling services carried out by students as peer counselors under the supervision of professional counselors. Peer counseling has an important role to play in promoting discipline among students (Osodo et al, 2016). Taking into account the importance of the role of peers, the development of a positive peer environment is an effective way that can be taken to support adolescent development.…”
Section: Smpn 30 Surabaya Is Located In the Medokanmentioning
confidence: 99%
“…Penelitian Bii, Aloka, and Raburu (2016) menjelaskan bahwa ada korelasi positif yang kuat antara konseling sebaya dan penyesuaian perilaku prososial. Penelitian J. M. Osodo et al (2016) menunjukkan bahwa konseling sebaya memiliki peran penting dalam mempromosikan disiplin diantara siswa di sekolah menengah umum. Penelitian ini merekomendasikan bahwa konselor sebaya harus termotivasi untuk tampil maksimal.…”
Section: Pendahuluanunclassified